Prediksi Persediaan Uang Cash Pada Bank Menggunakan Exponential Smoothing - Musthofa Galih Pradana; Pujo Hari Saputro ((JurTI) Jurnal Teknologi Informasi, 2023)
The position and existence of the money supply as an exchange rate makes its existence very important and vital. The existence and availability of money in the bank are important when many transactions involve cash. Activities in banking are inseparable from transactions involving cash. However, in practice, certain small and medium-scale banks do not provide large amounts of cash. Conditions for providing a large amount of cash will usually follow certain moments such as holidays, payment of monthly salaries, and other seasonal moments. In certain cases, cash withdrawals with a value above 100 million must be confirmed 1 day in advance. This raises the effectiveness value of the customer decreases. This problem can be helped by a predictive approach. The predictive approach has many algorithms or methods that can be used, one of the prediction methods applied is using Exponential Smoothing, the results show that the Single Exponential Smoothing method through measurements using Sum Square Error and Root Mean Square Error has advantages over Double Exponential Smoothing